Integritas Sufisme Dan Psikologi Transpersonal Eksplorasi Pengalaman Mistis Dalam Kesehatan Mental - Abbas, Faiz Musthofa (Tasamuh: Jurnal Studi Islam, 2025)
Transpersonal psychology places mystical experience as an essential dimension in the evolution of human consciousness. Sufism, as a manifestation of Islamic mysticism, offers a process of psychological transformation through fana' (the elimination of the ego) and baqa' (stable spiritual consciousness). This study analyzes the relationship between sufism and transpersonal psychology by examining the similarities between the concept of fana' and Maslow's self-transcendence and baqa' and Jungian individuation. Using critical literature studies, this study shows that mystical experiences in Sufism are not just spiritual phenomena, but psychological mechanisms that play a role in the regulation of emotions, the reconstruction of self-identity, and the optimization of mental well-being. Furthermore, Sufistic practices such as muraqabah and dhikr have parallels with mindfulness in modern psychotherapy, which has implications for the effectiveness of mindfulness-based therapy. These findings confirm that the integration of Sufism and transpersonal psychology can reconstruct contemporary psychotherapeutic approaches, presenting a more holistic and spirituality-based model of intervention.